Collaborative Regulation of Escherichia coli Glutamate-Dependent Acid Resistance by Two AraC-Like Regulators, GadX and GadW (YhiW) - Ma, Zhuo (American Society for Microbiology, 2002)
An important feature of Escherichia coli pathogenesis is an ability to withstand extremely acidic environments of pH 2 or lower. This acid resistance property contributes to the low infectious dose of pathogenic E. coli species. One very efficient E. coli acid resistance system encompasses two isoforms of glutamate decarboxylase (gadA and gadB) and a putative glutamate:γ-amino butyric acid (GABA) antiporter (gadC). The system is subject to complex controls that vary with growth media, growth phase, and growth pH. Previous work has revealed that the system is controlled by two sigma factors, two negative regulators (cyclic AMP receptor protein [CRP] and H-NS), and an AraC-like regulator called GadX. Earlier evidence suggested that the GadX protein acts both as a positive and negative regulator of the gadA and gadBC genes depending on environmental conditions. New data clarify this finding, revealing a collaborative regulation between GadX and another AraC-like regulator called GadW (previously YhiW). GadX and GadW are DNA binding proteins that form homodimers in vivo and are 42% homologous to each other. GadX activates expression of gadA and gadBC at any pH, while GadW inhibits GadX-dependent activation. Regulation of gadA and gadBC by either regulator requires an upstream, 20-bp GAD box sequence. Northern blot analysis further indicates that GadW represses expression of gadX. The results suggest a control circuit whereby GadW interacts with both the gadA and gadX promoters. GadW clearly represses gadX and, in situations where GadX is missing, activates gadA and gadBC. GadX, however, activates only gadA and gadBC expression. CRP also represses gadX expression. It does this primarily by repressing production of sigma S, the sigma factor responsible for gadX expression. In fact, the acid induction of gadA and gadBC observed when rich-medium cultures enter stationary phase corresponds to the acid induction of sigma S production. These complex control circuits impose tight rein over expression of the gadA and gadBC system yet provide flexibility for inducing acid resistance under many conditions that presage acid stress.